Agricultural groundwater management in the Upper Bhima Basin, India: current status and future scenarios - Lagudu, Surinaidu; Bacon, C.G.D.; Pavelic, Paul (Copernicus GmbH, 2013)
The basaltic aquifers of the Upper Bhima River basin in southern India are heavily utilized for small-scale agriculture but face increasing demand-related pressures along with uncertainty associated with climate change impacts. To evaluate likely groundwater resource impacts over the coming decades, a regional groundwater flow model for the basin was developed. Model predictions associated with different climate change and abstraction scenarios indicate that the continuation of current rates of abstraction would lead to significant groundwater overdraft, with groundwater elevations predicted to fall by -6 m over the next three decades. Groundwater elevations can however be stabilized, but would require 20-30% of the mean surface water discharge from the basin to be recharged to groundwater, along with reductions in pumping (5-10%) brought about by improved water efficiency practices and/or shifts towards lower-water use crops. Modest reductions in pumping alone cannot stabilize groundwater levels; targeted conjunctive use and improved water use efficiency are also needed.